Low-Temperature Decontamination with Hydrogen Peroxide or Chlorine Dioxide for Space Applications - Pottage, T. (American Society for Microbiology, 2012)
The currently used microbial decontamination method for spacecraft and components uses dry-heat microbial reduction at temperatures of >110°C for extended periods to prevent the contamination of extraplanetary destinations. This process is effective and reproducible, but it is also long and costly and precludes the use of heat-labile materials. The need for an alternative to dry-heat microbial reduction has been identified by space agencies. Investigations assessing the biological efficacy of two gaseous decontamination technologies, vapor hydrogen peroxide (Steris) and chlorine dioxide (ClorDiSys), were undertaken in a 20-m(3) exposure chamber. Five spore-forming Bacillus spp. were exposed on stainless steel coupons to vaporized hydrogen peroxide and chlorine dioxide gas. Exposure for 20 min to vapor hydrogen peroxide resulted in 6- and 5-log reductions in the recovery of Bacillus atrophaeus and Geobacillus stearothermophilus, respectively. However, in comparison, chlorine dioxide required an exposure period of 60 min to reduce both B. atrophaeus and G. stearothermophilus by 5 logs. Of the three other Bacillus spp. tested, Bacillus thuringiensis proved the most resistant to hydrogen peroxide and chlorine dioxide with D values of 175.4 s and 6.6 h, respectively. Both low-temperature decontamination technologies proved effective at reducing the Bacillus spp. tested within the exposure ranges by over 5 logs, with the exception of B. thuringiensis, which was more resistant to both technologies. These results indicate that a review of the indicator organism choice and loading could provide a more appropriate and realistic challenge for the sterilization procedures used in the space industry.